Studi Komparatif Sistem Pembuktian pada Peradilan Umum dan Peradilan Agama di Indonesia - Maryuliyanto Maryuliyanto; Ferika Nurfransiska; Wahyu Mustariyanto (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Evidence is the basis for judges in assessing facts and determining legal truth in resolving civil cases. Although General Courts and Religious Courts both use national civil procedural law, the characteristics of the Religious Courts' authority in handling cases of marriage, inheritance, and Islamic economics give rise to specificities in the application of evidence. This study aims to analyze the similarities and differences in the evidentiary systems in General Courts and Religious Courts and examine the challenges of evidence in the development of digital justice. The study uses normative legal methods with statutory, conceptual, and comparative approaches. Primary, secondary, and tertiary legal materials are obtained through literature studies and analyzed qualitatively through inventory, classification, interpretation, and comparison of legal norms. The results show that both judicial environments have similarities in the recognition of civil evidence based on national civil procedural law. The main findings indicate that differences in evidentiary practices lie more in the context of the application and assessment of evidence according to the characteristics of the case under the authority of each court. In addition, the development of e-Court, e-Litigation, and electronic evidence requires harmonization of evidentiary law to ensure legal certainty, justice, and the effectiveness of the judicial process.